ChemInform Abstract: Synthesis of 3‐Substituted 2‐Aminonaphtho[2, 3‐b]furan‐4, 9‐diones from 2‐Hydroxy‐1, 4‐naphthoquinone and Nitroalkenes. Issue 22 (3rd June 2014) - Zanwar, Manoj R.; Kavala, Veerababurao; Gawande, Sachin D.; Kuo, Chun‐Wei; Kuo, Ting‐Shen; Chen, Mei‐Ling; He, Chiu‐Hui; Yao, Ching‐Fa
Abstract A convenient method for the synthesis of naphthofuran diones (III) through condensation of 2‐hydroxy‐1, 4‐naphthoquinone with nitrostyrenes under aqueous conditions is reported.